(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To assess clinical and ultrastructural changes in the rabbit retina and choroid with an increase in the dose and number of intravitreal (IVit) melphalan injections. Material and Methods: Thirteen eyes of seven Chinchilla rabbits (age, 5–6 months; weight, 2.5–3 kg) underwent a clinical electron microscopy (EM) examination. Rabbit eyes were divided into five groups based on the dose and number of IVit melphalan injections given. Group 1 (4 eyes) received three 5-μg IVit melphalan injections; group 2 (2 eyes), two 10-μg injections; group 3 (2 eyes), two 20-μg injections; group 4 (3 eyes), two 30-μg injections; and group 5 (4 eyes), two 40-μg injections. The interval between IVit melphalan injections was one month. Enucleation was performed at week 4 after the last injection. Results: In group 1, ophthalmoscopic changes in the retina (small isolated areas of mild depigmentation) stayed the same until the end of the observation period. On EM, some retinal pigment epithelium (RPE) cells showed signs of destruction, whereas others showed signs of compensatory-and-restorative processes. In addition, discs of the outer segments (OS) of photoreceptors showed pathological changes varying in severity. Other photoreceptor layers and retinal neural cells showed no ultrastructural changes. In group 2, fundus changes were more severe than in group 1, and somewhat increased in severity with each injection. There was EM evidence of significant pathology in RPE cells, extracellular edema in the photoreceptor layer, damage to the photoreceptor inner segments and OS, and focal necrosis of the neural tissue. In group 3, there was retinal pigment redistribution after the first injection, with an increase in the degree and area of depigmentation after subsequent injections. In addition, EM found RPE cells showing various pathological changes (e.g., as severe as destruction), pigment granules scattered throughout the retina, and retinal gliosis due to growth of hypertrophic Müller cell processes. In groups 4 and 5, there were large regions of marked depigmentation which increased in area with each injection, becoming almost confluent, which resulted in a complete discoloration of the retina. In addition, EM found necrosis of RPE cells and photoreceptors and RPE cell debris in the inner retinal layers, and the outer and inner retinal layers were lost and replaced by glia. Ganglion cells exhibited signs of degenerative changes. The choroid showed almost complete loss of choriocapillaries with signs of destruction of choroidal vascular walls. Conclusion: We demonstrated experimentally that repeated IVit melphalan injections at various doses did not affect media transparency and the structure of the anterior segment of the eye, and produced no general toxic effects on experimental animals. The clinical and ultrastructural changes in the retina depended on the dose of melphalan, with repeated 5-μg and 10-μg IVit melphalan injections being relatively safe and causing mild changes only in the outer retinal layers. Care should be taken when using IVit melphalan injections at hig (20-μg – 30-μg) doses, taking into account that toxic changes with various degrees of degeneration (e.g., as severe as gliosis of the retina and destruction of some choroidal capillaries) can develop.